2012
DOI: 10.5194/acp-12-2713-2012
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ΔO<sub>2</sub>/ΔCO<sub>2</sub> ratios for the pollution events observed at Hateruma Island, Japan

Abstract: Abstract. Pollution events extracted from the in situ observations of atmospheric CO 2 and O 2 mixing ratios at Hateruma Island (HAT, 24 • N, 124 • E) during the period from October 2006 and December 2008 are examined. The air mass origins for the pollution events are categorized by using back trajectory analysis, and the oxidative ratios (OR = −O 2 :CO 2 molar exchange ratio) for selected pollution events are calculated. We find that there is a significant difference in the average oxidative ratios between ev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…The estimated uncertainty of the O 2 /N 2 scale stability (±0.45 per meg yr −1 ) discussed in Sect. 2.3, the uncertainty of the O 2 /N 2 span sensitivity (±3 %) and the uncertainty in the globally averaged APO associated with the limited atmospheric sampling (±0.2 PgC yr −1 ) discussed in Nevison et al (2008) were also included in the calculation of the uncertainties in APO. The uncertainties of α B and α F were ±0.10 (Keeling and Manning, 2014) and ±0.04 (Tohjma et al, 2008), respectively.…”
Section: Calculation Of Global Carbon Budgetsmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated uncertainty of the O 2 /N 2 scale stability (±0.45 per meg yr −1 ) discussed in Sect. 2.3, the uncertainty of the O 2 /N 2 span sensitivity (±3 %) and the uncertainty in the globally averaged APO associated with the limited atmospheric sampling (±0.2 PgC yr −1 ) discussed in Nevison et al (2008) were also included in the calculation of the uncertainties in APO. The uncertainties of α B and α F were ±0.10 (Keeling and Manning, 2014) and ±0.04 (Tohjma et al, 2008), respectively.…”
Section: Calculation Of Global Carbon Budgetsmentioning
confidence: 99%
“…Probably, an imbalance of the air-sea seasonal O 2 exchanges, outgassing flux associated with primary production in spring and summer, and ingassing flux associated with ocean ventilation in autumn and winter cause the interannual variations in Z. The results of ocean model simulations also support this mechanism (e.g., McKinley et al, 2003;Nevison et al, 2008). Therefore, it is difficult to estimate the shortterm carbon budgets unless the temporal variations in Z are accurately evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Goto et al 2017) and fossil fuel emissions (e.g. Minejima et al 2012). To observe the O 2 /N 2 ratio continuously, a commercially available fuel cell analyzer (Sable Systems, Oxzilla FC-II) has been widely used in recent studies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Piao et al (2008) suggested that the Northern Hemisphere terrestrial biosphere may be sequestering less carbon than previously thought, due to an increase in carbon losses during autumn, resulting from the strong dependence of respiration to rising temperatures; this conclusion was drawn from detrended atmospheric CO 2 data derived using a single digital filtering program . More recently, Minejima et al (2012) investigated the origin of pollution events at a Japanese island site that were identified from detrended atmospheric O 2 and CO 2 data using the Thoning et al (1989) program only.…”
mentioning
confidence: 99%